The Role of Surface Hydrophobization of Mild Steel by Some Triazole Derivatives in Acidic Medium - Plotnikova, M.D.; Shcherban, M.G.; Shitoeva, A.D.; Vasyanin, A.N.; Shein, A.B. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
Triazole derivatives (4,5-diphenyl-4H-1,2,4-triazole-3-thiol (4,5-PhTAT) and 3,4-diphenyl-5-(prop-2-yn-1- ylthio)-4H-1,2,4-triazole (3,4-PhPTTA) have been researched as corrosion inhibitors for mild steel in 0.1 N sulfuric acid solution. Electrochemical methods were used to estimate the corrosion rate and the inhibition efficiency: potentiodynamic polarization and impedance spectroscopy. The semi-empirical GFN2-xTB method, taking into account their implicit solvation in water using the ALPB method in the XTB program have been used for Geometry optimization of the structures of individual compounds and protomers in solution. Quantum chemical calculations suppose predominantly protonated structure for 3,4-PHPTTA molecules and neutral form of molecules for 4,5-PhTAT. According to electrochemical measurements the best inhibition efficiency for 4,5-PhTAT achieved at 50 mg∙l-1and 200 mg∙l-1 for 3,4-PhPTTA. 4,5-PhTAT and 3,4-PHPTTA are the mix-type inhibitors in 0.1 N sulfuric acid solution, but rate of cathodic process is decreased more than anodic. Contact angle measurements were carried out by the sessile drop method. Hydrophobization of the steel surface occurs in the blank acid and inhibited solution. The contact angle measurements by two test liquids (water and diethylene glycol) after corrosion with presents 4,5-Pstat and 3,4-PHPTTA show that the protective film formed in inhibited solution.
Keywords: corrosion; inhibitor; triazoles; polarization curves; surface tension; impedance spectroscopy; quantum chemical calculations; sessile drop method